Menggugat Kekuatan Patriarki: Hak-hak perempuan dalam transformasi menuju kesetaraan gender - Najwa Qurrata'Ayun; Siti eka Pratiwi; Asyifa Sari, Dini; Siti Noormala (PT. Sharia Journal and Education Center, 2024)
AbstractWomen can become strategic actors in development. Not only development in villages, but also national development that can change the lives of Indonesian people to become better and more prosperous. The article is the result of a literature review which attempts to fill the gap in studies regarding the transformation of women's roles as a form of resistance in the shackles of patriarchal culture which is still strong. The aim of the study is to identify the transformation of women's roles in several aspects that are still shackled by patriarchal culture. The library documents used include relevant books, journals, theses and theses. The results of the study explain that the position and role of women in society has experienced changes in several aspects, namely politics, education, economics and family, as well as social and cultural. The position and role of women cannot be marginalized by the power and domination of men. Women have succeeded in proving that their existence is worthy of being taken into account. The intelligence and expertise of Indonesian women, in particular, can no longer be underestimated because they have contributed to development. These findings are in line with the essence of women as social creatures who have the right to free expression, opinion, develop potential, etc.Keywords: patriarchal power, women's rights, gender equality AbstrakPerempuan bisa menjadi aktor strategis di dalam pembangunan. Tidak hanya pembangunan di desa-desa, tetapi juga pembangunan secara nasional yang dapat mengubah kehidupan masyarakat Indonesia menjadi lebih baik dan sejahtera. Artikel berupa hasil kajian literatur yang berusaha mengisi kekosongan studi mengenai bagaimana transformasi peran perempuan sebagai bentuk perlawanan dalam belenggu budaya patriarki yang masih kental. Tujuan kajian adalah mengidentifikasi transformasi peran perempuan pada beberapa aspek yang masih terbelenggu oleh budaya patriarki. Dokumen kepustakaan yang digunakan berupa buku, jurnal, tesis, dan skripsi yang relevan. Hasil kajian menjelaskan kedudukan dan peran perempuan di dalam kehidupan masyarakat telah mengalami perubahan pada beberapa aspek, yakni politik, pendidikan, ekonomi dan keluarga, maupun sosial dan budaya. Kedudukan dan peran perempuan tidak dapat dimarginalisasi dengan kekuasaan dan dominasi laki-laki. Perempuan berhasil membuktikan bahwasanya keberadaan mereka layak untuk diperhitungkan. Kecerdasan serta kepiawaian perempuan-perempuan Indonesia, khususnya, tidak bisa lagi dianggap remeh karena telah turut berkontribusi terhadap pembangunan. Temuan itu sejalan dengan hakikat perempuan sebagai makhluk sosial yang memiliki hak untuk bebas berekspresi, berpendapat, mengembangkan potensi, dan lain-lain. Kata Kunci : kekuatan patriarki, hak-hak perempuan, kesetaraan gender